Dimensão subjetiva da masculinidade: significações de homens gays sobre o papel da escola no processo de constituição da masculinidade - Amaral, Marcos Martins do (2019)
The constitution of gay masculinity is a complex and multidetermined process. We understand that school is an important social institution for the constitution of this individual and social phenomenon. The school presents itself as a contradictory space: at the same time that it disciplines the man for the heterosexuality - that is naturalized -, it opens possibilities for the first gay experiments. We seek to understand the constitution of gay masculinity from the experience that happens in school, giving centrality to social inequality - structural characteristic of Brazilian society and that has produced unequal schooling processes. In this sense, the constitution of the masculinity of rich and poor gays presents itself differently. The work has as its main objective the study of the subjective dimension of gay masculinity. Considering the possibilities and limitations of such a large study, it was intended to investigate the meanings of students, rich and poor, self-declared gay, about the role of school in the constitution of masculinity and, thus, to give visibility to aspects that make up the subjective dimension of the phenomenon. This work is based on the theoretical-methodological framework of Socio-Historical Psychology, starting from a materialist, historical and dialectical notion of reality, in an effort to overcome the subjectivist and objectivist theories of the psychological field that tend to naturalize the social phenomena. We conducted two conversations with two groups of self-declared gay teenagers, poor and rich, from the High School of Sao Paulo, separately. The conversations were analyzed from the constitution of Nuclei of Meaning. The dialectical movement of analysis has allowed us to affirm that the school, with all its contradictions, is an important social institution in the constitution of the masculinity of gay adolescents and must overcome, institutionally, its estrangement from its social functions